1998
DOI: 10.1093/emboj/17.13.3619
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel stress-induced genes downstream of chop

Abstract: CHOP (GADD153) is a small nuclear protein that dimerizes avidly with members of the C/EBP family of transcription factors. Normally undetectable, it is expressed at high levels in cells exposed to conditions that perturb protein folding in the endoplasmic reticulum and induce an endoplasmic reticulum stress response. CHOP expression in stressed cells is linked to the development of programmed cell death and, in some instances, cellular regeneration. In this study, representational difference analysis was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
251
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(260 citation statements)
references
References 49 publications
8
251
1
Order By: Relevance
“…58 Using representative difference analysis, Ron and colleagues found three target genes of CHOP that they referred to as DOCs (for downstream of CHOP). 60,61 DOC1 is a stress-inducible form of carbonic anhydrase VI, which is predicted to increase the proton concentration and to decrease intracellular pH. DOC4 is a homologue of Tenm/Odz, which might function in signaling at compartment boundaries.…”
Section: Downstream Of Chop In Er Stress-induced Apoptosismentioning
confidence: 99%
“…58 Using representative difference analysis, Ron and colleagues found three target genes of CHOP that they referred to as DOCs (for downstream of CHOP). 60,61 DOC1 is a stress-inducible form of carbonic anhydrase VI, which is predicted to increase the proton concentration and to decrease intracellular pH. DOC4 is a homologue of Tenm/Odz, which might function in signaling at compartment boundaries.…”
Section: Downstream Of Chop In Er Stress-induced Apoptosismentioning
confidence: 99%
“…Similarly to ATF6, the IRE1 fragments enter the nucleus and upregulate ER stressresponsive genes. 65 The IRE-mediated response is, however, slower than that mediated by ATF6, because it occurs via processing the mRNA for XBP1, which is induced by active ATF6. Splicing of a small intron from the XBP1 mRNA is carried out by the ribonuclease activity of IRE1 and generates an active transcription factor.…”
Section: Gangliosides and The Er Stress Responsementioning
confidence: 99%
“…18 Because CHOP functions as a transcription factor, there must be a target gene(s), the transcription of which is activated by CHOP, and whose product(s) functions in the apoptosis signal cascade. Wang et al 19 found candidate target genes of the CHOP protein when using representational difference analysis. However, these genes are distinct from known factors involved in the ER stress response and apoptosis.…”
Section: Introductionmentioning
confidence: 99%